Climate change aggravating migration and health issues in the African context: The views and direct experiences of a community of interest in the field - Ursula Trummer; Thowaiba Ali; Davide Mosca; Blessing Mukuruva; Hadijah Mwenyango; Sonja Novak-Zezula (Journal of Migration and Health, 2023)
Climate change is an increasingly important theme in Africa, where a large majority of its people depend on livestock and agricultural activities for livelihood. Concurrently, the topic of health of migrants and people on the move is rapidly raising both in the health debate and migration governance agenda in the Region. The link with climate change from the perspective of health and migration experts needs to be systematically addressed. Objectives: The article aims to contribute to the discourse on the interrelation of climate change, migration, and health by providing contributions of experts in the field of health and migration directly working with migrant and refugee communities in Africa. Methods: A webinar was conducted to collect and discuss first-hand experience with 25 participants from a postgraduate online course on health and migration funded by the Austrian Government and implemented in a co-operation of the Center for Health and Migration, Austria, with Makerere University, Uganda, the International Organization for Migration – UN Migration, and Lancet-Migration. As a result from the discussions, two cases from Sudan and Zimbabwe were selected to be further analysed with desk research to illustrate and underpin the points made. Results: All webinar participants reported to encounter climate change effects on health and migration in their professional practice. In their experience, climate change aggravates issues of health and migration by fueling forced migration and displacement, increasing health care needs, and deteriorating access to health care. Specific health challenges were identified for mental health problems caused by effects of climate change-induced migration, which remain widely undiagnosed and untreated, and the special affectedness of women and girls, with their mental, sexual and reproductive health severely deteriorated in insecure environments. The case studies from Sudan and Zimbabwe underline these observations. Conclusions: The interplay of effects of climate change, (internal) migration, and health is reported by a community of experts in the field of health and migration who are residing in Africa and working with migrant communities. Webinars prove to be an easy to implement tool to collect first hand evidence from practice experts, to foster exchange of experiences, and to get people engaged in further collaboration and discussion.